Influence of Ta5+ content on the crystallographic structure and electrical properties of [001]PC-oriented (Li, Na, K)(Nb, Ta)O3 single crystals. Issue 12 (29th February 2016) - Liu, Hairui; Veber, Philippe; Koruza, Jurij; Rytz, Daniel; Josse, Michael; Rödel, Jürgen; Maglione, Mario
Abstract : A series of centimeter-sized lead-free piezoelectric Li + - and Ta 5+ -modified (Na, K)NbO3 single crystals with an ABO3 perovskite structure was successfully grown by the top-seeded solution growth method. Abstract : A series of centimeter-sized lead-free piezoelectric Li + - and Ta 5+ -modified (Na, K)NbO3 single crystals with an ABO3 perovskite structure was successfully grown by the top-seeded solution growth method. Effective segregation of the elements was considered in order to further develop the growth of Li + - and Ta 5+ -modified (Na, K)NbO3 single crystals. The crystallographic structure and electrical behaviour along the [001]PC orientation were studied. X-ray diffraction, Raman spectroscopy and dielectric studies reveal that the increase in Ta 5+ content reduces the orthorhombic–tetragonal phase transition. Bipolar and unipolar strain curves were investigated at 2 kV mm −1 . The highest bipolar and unipolar strains associated with a large-signal piezoelectric constant of 368 pm V −1 were achieved for Li0.02 Na0.626 K0.354 Nb0.808 Ta0.192 O3 . The asymmetric bipolar strain curves were observed and related to the existence of internal bias fields induced by defect dipoles, which were created during the crystal growth process.